ANALISIS IMPLEMENTASI APLIKASI ELECTRONIC COMMERCE PADA MELI CAKE BERBASIS WEB MOBILE DENGAN KONSEP BUSINESS to CONSUMER - Meli Erpiyana; Helisia Margahana; Muhammad Junaidi (Jurnal Signaling, 2018)
Electronic Commerce is one of the developments in technology and the internet, which is an internet service that is utilized for buying and selling online. Electronic commerce can involve electronic funds transfer, electronic data exchanges, automated inventory management systems and automated data collection systems. This research was conducted to design and build mobile web-based E-commerce applications with the B to C concept after testing using mobile information systems. Data collection uses observation, interview and literature study. The implementation of this mobile web-based application was designed using the Hypertext Preprocesseor programming language and My Structured Query Language. This design model uses the waterfall method by conducting a case study research that analyzes how to make it easier for consumers to obtain information about goods offered by the cake shop from the system that has been made can be concluded, in terms of the product sales process, product information, and the ordering process products desired by consumers implementing e-commerce with the BtoC concept increase consumer confidence by taking into account the determinants of trust such as maintaining reputation by providing reliable services, maintaining customer satisfaction.